Evaluation of a hepatitis B vaccination program in Chiang Mai, Thailand - Prapan Jutavijittum (2018)
Chiang Mai is a province in northern Thailand that started a vaccination program for hepatitis B virus (HBV) infection in 1989. In this paper, we report the long-term efficacy of this program. Of children aged 4-9 years, 65.7% had a complete course and 3.8% had an incomplete vaccination course. Urban schoolchildren had higher percentage of HB vaccination than rural schoolchildren (89.1% vs 46.9% for the complete course, p < 0.001). The overall prevalence rate of HBsAg in Chiang Mai schoolchildren was 1.2%, with no significant differences between gender (p = 0.496) and school areas (p = 0.477). Anti-HBc antibodies were detected in 6.9% of children. Overall, 26.2% of children had protective levels of anti-HBs antibodies (≥ 10.0 m mlU/ml), and 11.2% had low levels of these antibodies (1.0-9.9 mlU/ml). Compared to previous reports, our results show a lower percentage of anti-HBs antibodies, 33.8% of children age 4 years had protective anti-HBs antibodies, dropping to 18.4% by age 9 years. Among those anti-HBs seropositive, 9.1% were anti-HBc positive, indicating a natural infection with HBV. We found a small number of children, despite adequate immunization, developed HBV infection.